ECONOMIC VALUATION OF CORAL REEFS ECOSYSTEM OF BANGSRING, BANYUWANGI, INDONESIA - Muhammad Arif Asadi; Anthon Andrimida (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Coral reefs ecosystem of Bangsring provide both commercial and non-commercial goods and services. Local fishermen rely on reef fisheries while tourism activities have been growing in this area. Seeing that the economic benefits derived from coral reefs are vital to the economies of Bangsring communities, economic valuation of these benefits is necessary to guide sustainable and wise use of these resources and to provide useful information for improved decisions. The research was conducted between June 29and August 9 of 2015 aimed to estimate the total economic value (TEV) of coral reefs of Bangsring, Banyuwangi Regency, included passive use values and direct use values. The research was a participatory case study where primary and secondary data were collected using the purposive sampling technique. The study revealed that the estimated TEV of the coral reefs of Bangsring was IDR 41.6 billion per year or IDR 3.2 billion per hectare per year with tourism contributing 60 % or IDR 25 billion per year of the TEV. The healthy coral reefs of Bangsring support local communities and generate billions of rupiahs annually; therefore, it is critical to manage the coral reefs of Bangsring sustainably for current and future generations.